ANALISIS E-WALLET BERBASIS TAM (TECHNOLOGY ADOPTION MODEL) DI PT TELKOM INDONESIA TBK - Rivanda Arvyana; Fenny Damayanti; T Sitti Rochmah (JURNAL LENTERA BISNIS, 2022)
More and more internet users have made actors in the field of technology to continuously create innovations so that smartphone users can make the best use of technology. One of them is by issuing a product called e-wallet which is a trend in carrying out all payment transaction activities and purchasing items. Likewise with PT Telkom which participated in implementing government policies in reducing the use of cash. By using the e-wallet application owned by PT Telkom, this research is focused on the use of TAM-based e-wallet. In conducting this research, the methodology used is by using a qualitative methodology and through a descriptive approach and using data collection techniques through literature studies. There are many benefits and also the convenience of using Telkom's e-wallet or commonly known as t-money. With various features in the application, users can make bill payment transactions as well as purchase train or plane tickets, merchants, and make purchases of electricity pulses or data packages. To be able to win the competition in the business world, PT Telkom must continue to improve the features available in the e-wallet application. That way users can feel the benefits of using the application. This can be used by Telkom to provide testimonials to other users.Keywords: Fintech, E-wallet, TAM